Campylobacter infection in a cohort of rural children in Moramanga, Madagascar - Randremanana, Rindra Vatosoa (BioMed Central, 2014)
BACKGROUND: Campylobacter infection is the most common cause of bacterial gastroenteritis in developing countries, including Madagascar. Reports of pathogenicity have not been consistent and repeated exposures over time seem to lead to the development of protective immunity in developing areas. We conducted this study to support evidence for these hypotheses by exploring the association between infection and age, the reoccurrence of infection and the pathogenicity of Campylobacter. METHODS: We carried out a community-based longitudinal study of children under the age of 24 months in two rural villages in Moramanga, Madagascar. Children were visited twice a week and a stool specimen was collected in cases of diarrhoea. Stools specimens were collected bimonthly from all children enrolled, regardless of symptoms. Children were followed-up until the age of 36 months. RESULTS: Between January 2010 and May 31(st) 2012, 508 children were included in the cohort. We detected 319 episodes of Campylobacter infection in total, and 43.3% (n = 220) of the children had at least one episode of intestinal Campylobacter infection. The rate of Campylobacter isolation from stool specimens was 9.3%. The annual incidence rate for symptomatic Campylobacter infection was 0.05 episodes/child. The probability of Campylobacter infection was highest between the ages of six and 23 months. Taking children under six months of age as the reference group, the age-specific odds ratio for the association was 5.0 (95% CI: 2.9-8.6) for children aged six to 11 months, 5.7 (95% CI: 3.3-10.0) for children aged 12 to 17 months and 3.3 (95% CI: 1.8-5.8) for children aged 18 to 23 months. A second episode of infection occurred 63 days after the first episode in children with primary infections, and after 137 days in children with multiple infections (p < 0.01). First episodes of Campylobacter infection were associated with diarrhoea (odds ratio = 16.1; 95% CI: 1.8-140.8). CONCLUSION: Our findings suggest that protective immunity to Campylobacter may be acquired over time, following repeated exposures. However, Campylobacter infection prevention measures should be reinforced in the first year of life, as this age seems to be associated with the highest risk of diarrhoea during Campylobacter infection.